Breast Geometry and Sports Bra Design Study for Adolescent Girls (Journal of Fiber Bioengineering and Informatics, 2024)
Breast measurement presents a complex challenge in the design of sports bras, particularly for adolescentgirls whose bodies are rapidly changing. This study aimed to explore breast anthropometry amongadolescents. A survey involving 23 girls aged 10 to 14 assessed their understanding of bra-relatedproblems. In comparison, a wear trial with 7 girls sized 30AA to 32A evaluated their preferencesthrough five bra conditions, 3D scanning and questionnaires. The study revealed a significant knowledgegap, with only 8.7% having had a bra fitting and less than half knowing how to determine their brasize. Notably, the upper bust measurement was significantly correlated with the level of “coolness”($r=−0.395$ and $p = 0.038$), and the under bust measurement was correlated with the level of “comfort” $(r = −0.441$ and $p = 0.019).$ The findings suggest a need for breathable fabrics in the upper bustwhile a preference for a stretchable underband to accommodate body growth. These results highlightthe need to design sports bras tailored to the unique needs of adolescent girls, providing designerswith critical insights into the necessary features and dimensions for optimal comfort during physicalactivity.
Keywords: Breast Shape; Body Measurement; 3D Scan; Subjective Questionnaire; Early Bra Education.